Systematic Literature Review: Role of Reinforcement In Intrinsic and Extrinsic Motivation - Miladiah, Fakhriatul Ulfa; Fithri, Rahma; Lestari, Yuliana Intan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Learning motivation is a crucial foundation for the academic success of elementary school students, yet low motivation remains a primary challenge in educational practice. Although the behavioristic approach through reinforcement offers a practical solution, empirical findings on its effectiveness show inconsistencies, particularly in differentiating its influence on intrinsic and extrinsic motivation. This study aims to synthesize empirical findings on the influence of reinforcement on the learning motivation of elementary school students. The method used is a systematic literature review of seven articles from the Google Scholar and Sage Publications databases that met the inclusion criteria. The synthesis results indicate that reinforcement is a fundamental factor that significantly shapes behavior and enhances motivation. Positive reinforcement, such as praise, is proven effective in strengthening perceived competence, whereas criticism has the potential to damage learning interest. Its effectiveness is highly dependent on crucial factors such as timing, consistency, and appropriateness to student characteristics. This study confirms that reinforcement, when applied strategically and wisely, is an applicable and relevant tool for teachers to create a supportive learning environment that fosters the development of student motivation.